1998
DOI: 10.4012/dmj.17.205
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Viscoelastic Properties in Torsion of Four Commercially Available Resins for Crown and Bridge.

Abstract: In order to clarify the viscoelastic properties of four commercial resins for crown and bridge, the dynamic shear modulus (G'), Knoop hardness (KHN), filler content, quantity of unreacted substance and thermal expansion were measured. The results were as follows. The G' (37•Ž) of each material ranged from 2.61•`11.1GPa, and gradually decreased with increasing temperature. KHN (23•Ž) ranged from 29.4 to 120, and the most significant correlation (0.999) was found between G' and KHN. Of the relationship among G',… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…18 The increased practice of using a veneering technique with indirect composite resins is due to recent improvements in the composite resins. 27,37 These new composite resins have an approximately 66% volume percentage of inorganic ceramic fillers, which results in improved mechanical properties with a flexural strength of between 120 and 160 MPa and an elastic modulus of 8.5-12 GPa. 12 Most veneering composite resins are applied with a post-curing process through heat and photo-polymerization, which results in superior flexural strength to veneering ceramic, minimal polymerization shrinkage, and a wear rate comparable to tooth enamel.…”
Section: Introductionmentioning
confidence: 99%
“…18 The increased practice of using a veneering technique with indirect composite resins is due to recent improvements in the composite resins. 27,37 These new composite resins have an approximately 66% volume percentage of inorganic ceramic fillers, which results in improved mechanical properties with a flexural strength of between 120 and 160 MPa and an elastic modulus of 8.5-12 GPa. 12 Most veneering composite resins are applied with a post-curing process through heat and photo-polymerization, which results in superior flexural strength to veneering ceramic, minimal polymerization shrinkage, and a wear rate comparable to tooth enamel.…”
Section: Introductionmentioning
confidence: 99%
“…The application of indirect composite materials for tooth-colored restorations has increased substantially. This trend is probably due to improvement in the properties of composite materials (1)(2)(3). Despite the improvement in properties and clinical results, several factors which deserve attention have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it can be presumed that the refractive index and temperature dependence of a composite resin are controlled by those of the base resin, which is main structure of a composite resin. On the other hand, a previous study 22) reported that the linear-thermal expansion coefficient of the four commercial composite resins ranged from 17.0×10 −6 /ºC to 39.0×10 −6 /ºC. This means that the cubic-thermal expansion ranged from 0.39 to 0.89% at 4-80ºC.…”
Section: Discussionmentioning
confidence: 84%